Gas exchange, chlorophyll fluorescence, biomass production, water use and yield response of tomato (Solanum lycopersicum) grown under deficit irrigation and varying nitrogen levels - BAHADUR, ANANT; LAMA, T D; CHAURASIA, S N S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment on irrigation schedulings and nitrogen rates was conducted to study the physiological, growth and yield responses of tomato (Solanum lycopersicum L.) under deficit irrigation and various N levels. Results obtained indicated that irrigation at 10 or 20 days (I1 and I2) interval had significantly higher gas exchange (photosynthesis rate, stomatal conductance and transpiration rate), photochemical efficiency of PS II (Fv/ Fm), RWC, leaf area, chlorophyll content and fruit production over 30 days irrigation interval (I3). Nitrogen application had also significant effects on most of the physiological, growth and yield traits at 45 and 75 DAT, however N at 120 kg/ha had noticed maximum gas exchange, Fv/Fm, leaf area, CCI and fruit production over other two N levels. Interaction of I x N had exhibited significant effect on few parameters such as; photosynthesis rate, stomatal conductance, leaf area and weed growth, particularly at 45 DAT. Biomass production and partitioning in various plant parts were varied significantly, and under moderate water deficit with higher N levels (I2 N1 and I2 N2), an optimum allocation of biomass (less in roots and stems and higher in fruits) was registered. The maximum WUE (14.19 q/ha/cm) was reported with irrigation scheduling at 20 days, besides 36% water savings over I1. For realisation of higher WUE, tomato should be irrigated at 20 days intervals with N application at 120 kg/ha.